Examining the relationship between oral health promoting behaviour and dental visits - Alayadi, Haya; Bernabe, Eduardo; Sabbah, Wael (International Journal of Health Sciences, 2019)
Objective: The objective of this study was to explore the relationship between a number of health-promoting behavior and dental visits. Materials and Methods: A stratified sample from 16 primary schools in Riyadh was selected. A total of 1087 students aged 6–12 years were included in the study between October 2017 and January 2018. The World Health Organization (WHO) criteria for assessing dental caries were used to collect clinical data. Information on dental visits and health-promoting behaviors were collected through modified WHO questionnaire. An aggregate variable of eleven health-related behaviors was created. Logistic regression model was used to examine the relationship between regular dental visits and the aggregate health behavior variable accounting for age, sex, parental education, family income, and caries experience. Results: Only 6.8% of the sample reported regular dental visits. The logistic regression showed that the aggregate variable of health-promoting behavior was significantly related to regular dental visits with odds ratio 1.23 (confidence interval 95% 1.10–1.39). Other variables significantly related to regular dental visits included sex (female), higher family income, and lower mean of caries experience. Conclusion: Despite the availability of free dental services in Saudi Arabia, most of the dental visits are symptomatic. The observed association between health-promoting behaviors and regular dental visits implies that those at higher risk of oral diseases are less likely to visit a dentist regularly.